Analysis Of The Influence Of Segmenting, Targeting, And Positioning On Purchasing Decisions At Pondok Salero Restaurant, Kediri - Alwi, Muhammad; Hakimah, Ema Nurzainul (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim :The purpose of this study was to determine the influence of segmenting, targeting, and positioning on purchasing decisions at the Pondok Salero Kediri restaurant. Design/Method/Approach :The method used in this research is quantitative.Sampling technique using technique accidental sampling. The sample taken in this study were consumers who bought Padang cuisine at Pondok Salero Restaurant, Kediri, totaling 40 people. The measurement used in this study was by using the SPSS version 25 analysis tool. Research Findings :The results of the t-test study indicate that the segmenting, targeting, and positioning variables partially have a significant effect on purchasing decisions. Based on the results of the F test, it is known that the segmenting, targeting, and positioning variables simultaneously have a significant effect on purchasing decisions. Theoretical contribution/Originality :segmenting, targeting, and positioning play a role as the basis for creating an effective and efficient marketing strategy. By dividing the market into relevant segments, selecting potential segments, and strategically positioning the menu, STP helps Pondok Salero Kediri restaurant significantly influence consumer purchasing decisions. Practitionel/Policy implications:Implementing the right STP strategy, Pondok Salero Kediri restaurant can better understand market needs, target the right segment, and create an attractive image. Efforts such as providing relevant menus, attractive promotions, and satisfying dining experiences can increase customer purchasing decisions while creating long-term loyalty. Research limitations:Because this study proves that there are still other variables that influence purchasing decisions, this can be used as material for conducting similar further research to obtain better results. Keywords :segmenting, targeting, positioning and purchasing decisions